PENGARUH KOMPETENSI DAN PROFESIONALISME AUDITOR INTERNAL TEHADAP KINERJA KARYAWAN DENGAN INTERNAR KONTROL SEBAGAI VARIABEL INTERVENING - Muh. Akob; Ansir Launtu; Irwan AS (Faculty of Economics and Business, Universitas Malikussaleh, 2019)
This study aims to determine the effect of competence and professionalism of internal auditors on the performance of Employees with Internal Control as Intervening Variables. The research sample consisted of 96 Kalla Group employees who were directly involved in the finance department. The questionnaire was tested for validity and reliability test before research. The analysis prerequisite tests used were normality test, linearity test, mulitikolonieritas test and heteroscedasticity test. Analysis of the data used is simple regression analysis and multiple regression analysis. The results showed (1) There was a significant positive effect on internal auditor competency on employee performance; (2) There is a significant positive effect of internal auditor professionalism on performance; (3) There is a significant positive effect of internal control on employee performance (4) There is a significant positive effect on internal auditor competence on internal control; (5) There is a significant positive effect on the professionalism of internal auditors on internal control; (6) There is a significant positive effect of internal auditor competence on employee performance through Internal control as an intervening variable; (7) There is a significant positive effect of internal auditor professionalism on employee performance through Internal Control as an Intervening variable.